Study of Non Performing Financing in Islamic Bank: The Role of Internal and External Ratio - Asiyah, Binti Nur; Subagyo, Rokhmat; Andayani, Dwi; Wahyudi, Amin; Holle, Mohammad H.; Sulistiani, Endah (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 3 (2023): The 6th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2023)
This study aims to analyze financing problems in Islamic banks, namely Bank Muamalat Indonesia, which has a tendency of increasing financing problem. This situation is reviewed from the internal indicators of Islamic Banks, namely the Minimum Capital Adequacy Requirement, Financing to Deposit Ratio, Return on Assets, Operational Costs to Operating Income and indicators of external conditions in the form of Inflation, and Exchange Rates. This study uses a quantitative approach, precisely the associative research. The secondary data were collected from 36 samples, taken from the 2013-2021 data of Bank Muamalat Indonesia. The sampling technique uses a saturated sample. The multiple linear regression analysis was applied. The results show that, internal indicators, namely the Minimum Capital Adequacy Requirement, have no significant negative effect on Non-Performing Financing; Financing to Deposit Ratio has a significant positive effect on Non Performing Financing; Return on Assets has a significant negative effect on Non Performing Financing and Efficiency Ratio/BOPO has an insignificant negative effect on Non Performing Financing. External indicators include inflation but no significant negative effect on non-performing financing; Exchange Rate has no significant positive effect on Non Performing Financing. The practical implications of this research are the internal indicators to watch out for, namely the availability of capital, while the external indicators are the exchange rate so that it is significant in reducing problem financing.